Adherence to transcranial Doppler screening guidelines among children with sickle cell disease1. Issue 2 (28th June 2012) - Eckrich, Michael J.; Wang, Winfred C.; Yang, Elizabeth; Arbogast, Patrick G.; Morrow, Anthony; Dudley, Judith A.; Ray, Wayne A.; Cooper, William O.
Abstract Background Little is known about adherence to guidelines recommending yearly screening with transcranial Doppler (TCD) ultrasonography to detect stroke risk for children with severe sickle cell disease. The objective was to determine the proportion of children with hemoglobin SS (HbSS) or sickle‐β0‐thalassemia (HbSβ0) aged 2–16 years who received recommended TCD screening from 1997 to 2008, and to identify factors associated with adherence. Procedure A retrospective cohort study included patients enrolled in Tennessee Medicaid with HbSS or HbSβ0 who received care at the two largest sickle cell centers in Tennessee. The outcome of interest was adherence with guidelines for annual screening TCD's, identified from computer claims and validated through medical record review. The cumulative rate of children who received a TCD per year was calculated using the Kaplan–Meier method. Cox proportional hazards regression was used to examine the association of child, family, and health care use characteristics with receiving a TCD. Results Among 338 TCD eligible at‐risk children, 232 (68.6%) had at least one TCD during the study period. The yearly cumulative incidence of annual TCD's increased from 2.5% in 1997 to 68.3% in 2008. In multivariate models, calendar year, maternal education, and increased number of sickle cell related outpatient visits were associated with an increased rate of receiving a TCD. Conclusions Publicly insured children with HbSS or HbSβ0 had increasing adherence with TCD screening guidelines between 1997 and 2008, though 31% had no TCD at all during follow‐up. Increasing number of sickle cell related outpatient visits was associated with increasing adherence to screening guidelines. Pediatr Blood Cancer 2013;60:270–274. © 2012 Wiley Periodicals, Inc.